Organisational Management Training for ISMAU Banjarnegara Administrators to Improve Organisational Management Effectiveness - Solechan Solechan; Beny Sintasari; Zahrotun Ni’mah Afif; Ubaidillah Ubaidillah; Ari Kartiko; Muhammad Fadhlan Refa (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2026)
Organisational performance is greatly influenced by the capacity of administrators to perform managerial functions effectively, particularly in planning, organising, implementing, and evaluating activities. This community service aims to improve the effectiveness of organisational management through organisational management training for ISMAU Banjarnegara administrators. The data were analysed descriptively and qualitatively to examine changes in the understanding, attitudes, and managerial skills of the administrators. The results of the service showed that the training contributed to an increase in the administrators' ability to formulate the objectives and direction of the organisation's programmes, divide roles and responsibilities more clearly, and develop more structured work coordination mechanisms. The administrators also began to understand the importance of documentation and evaluation as part of the organisational management cycle. In addition, the training encouraged the formation of a more systematic and accountable work pattern in the implementation of organisational programmes. These findings indicate that organisational management training not only improved the administrators' conceptual understanding but also strengthened the organisational management practices of ISMAU Banjarnegara in a sustainable manner.